The Quality Control Program for Industrial Hygiene Laboratories in Korea - Hae Dong Park; Eun Kyo Chung; Kiwoong Kim (Elsevier, 2017)
In 1992, the quality control program was introduced in Republic of Korea to improve the reliability of the work environment monitoring, which was introduced in the 1980s. The commission entrusted by the Ministry of Employment and Labor, the Occupational Safety and Health Research Institute has conducted the program for industrial hygiene laboratories including designated monitoring institutions and spontaneously participating agencies. The number of institutions that participated in the program has increased from 30 to 161. The initial conformance ratio in the participants was 43% (organic solvents) and 52% (metals). Thereafter, the conformance ratio increased rapidly and it has remained in a stable state at more than 89% since 1996. As subject materials, 13 kinds of organic solvents and 7 kinds of metals were used. To improve the capability of measurement and analysis of private institutions, educational courses were conducted annually. An assessment at the actual sites of participants was additionally introduced into the program in 2013. Thus, the program turned into a system that administrates the overall process of participants. For the future, the scope of target materials will be extended through additional items. Thus, the reliability of the results of the work environment monitoring is expected to increase accordingly.